Forensic short tandem repeat markers alteration in leukemia cells and breast cancer tissues - Omar, Izzah Syahira (2025)
Cancer is a significant concern in Malaysia, influenced by genetic defects from heredity and environment. Recent cancer research has focused on short tandem repeat (STR) markers for alteration studies in both solid and blood cancers. STRs, characterized by repetitive sequences with short repeat motif units, area valuable for forensic identification and paternity testing due to their high polymorphism. In diagnostic pathology, STR analysis could aid in tissue identification, addressing sample mislabelling and contamination. However, applying STR markers to cancerous tissues is challenging due to microsatellite instability (MSI) and loss of heterozygosity (LOH), which can affect STR genotyping. Despite their utility, there is a gap in understanding STR alterations across different molecular subtypes of breast cancer and leukemia. Therefore, this study aims to investigate the prevalence of STR alterations on breast cancer and leukemia sample tissues using QIAGEN Investigator 24plex QS kit. A total of 85 samples were genotyped, comprising 20 paired formalin-fixed paraffin-embedded (FFPE) breast cancer tissues and their corresponding normal adjacent tissues, 20 blood samples and five buccal swab samples from leukemia patients, and 20 blood samples from unrelated healthy individuals serving as controls. The findings revealed that among the four molecular subtypes of BC tissues, Luminal A subtype exhibited the highest LOH rate, while basal cell-like subtype displayed had highest MSI rate. No significant genetic alterations were found between the paired leukemia and their normal tissue samples but the D19S433 locus was significantly associated with leukemia compared to unrelated normal control. In summary, the genetic instability observed in human carcinomas has been recognized and may present difficulties for forensic genotyping and DNA profile comparison.